pyGeno: A Python package for precision medicine and proteogenomics [version 2; peer review: 1 approved, 2 approved with reservations] - Daouda, Tariq; Perreault, Claude; Lemieux, Sébastien (F1000 research, 2016)
pyGeno is a Python package mainly intended for precision medicine applications that revolve around genomics and proteomics. It integrates reference sequences and annotations from Ensembl, genomic polymorphisms from the dbSNP database and data from next-gen sequencing into an easy to use, memory-efficient and fast framework, therefore allowing the user to easily explore subject-specific genomes and proteomes. Compared to a standalone program, pyGeno gives the user access to the complete expressivity of Python, a general programming language. Its range of application therefore encompasses both short scripts and large scale genome-wide studies.